The development of a device for the investigation of dorsiflexion range of the ankle with a capacity to measure pathology, recovery and pharmacological benefit - Botha, Jan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2005.